Research highlights: Applications of atomic force microscopy in natural and engineered water systems - Zhu, R.; Tan, D.T.; Shuai, D. (Royal Society of Chemistry, 2016)
The mechanistic understanding of the fate, transport, and transformation of contaminants in natural and engineered water systems is of great importance for environmental remediation. Recently, atomic force microscopy (AFM) has emerged as a promising tool to provide insights on the properties and interactions of materials, chemicals, and microorganisms. This article highlights three studies using AFM to understand the molecular mechanism of membrane fouling for water and wastewater treatment, to characterize biofilm properties that influence the accumulation and release of pathogens in drinking water distribution systems, and to evaluate the nucleation and growth of manganese (Mn) (hydr)oxide for remediating Mncontaminated environmental systems.